Quantification of mechanical compaction and cementation during contact metamorphism of sandstone. (July 2020) - Girnun, Joshua; Emmanuel, Simon; Levenson, Yael; Anovitz, Lawrence M.
Abstract: Both mechanical compaction and mineral reactions reduce the porosity and permeability of sedimentary rocks. These processes occur during burial and diagenesis, as well as during contact and regional metamorphism. Although the mechanisms governing porosity reduction have been studied extensively in diagenetic sedimentary systems, relatively limited work has been carried out on metamorphic rocks. Here, we present a petrographic method to isolate and quantify the effects of mineral cementation and mechanical compaction in sandstone altered during contact metamorphism. We sampled rocks from the Inmar formation in Makhtesh Ramon (Israel) - where indurated sandstone is present near contacts with dykes – and analyzed them using high resolution scanning electron microscopy and cathodoluminescence. Using image segmentation to differentiate between quartz cement and detrital grains, we observed both grain rearrangement and brittle fracturing near intrusive contacts. At the highest level of porosity reduction, mechanical compaction reduced porosity by 18–31%, while cementation caused a reduction of 11%. We also found that the maximal level of mechanical compaction, as well as its spatial extent, scale with the size of the intrusion. By contrast, the maximal level of cementation was unaffected by the size of the dyke. Our findings demonstrate that to model porosity and permeability evolution in contact aureoles, both mechanical and chemical processes must be taken into account. Highlights: Mechanical compaction and cementation reduce sandstone porosity during contact metamorphism. Mechanical and chemical processes reduced porosity by up to 18–31% and 11% respectively. Size of intrusion determines spatial extent and maximal level of mechanical compaction. Petrographic method indicates maximum pressure of 105 MPa at contact.